The Responsibility of Limited Liability Company Organs in Group Company (Holding) of State-Owned Enterprises - Dahana, Thomas Nanda; Santoso, Budi; Prananingtyas, Paramita (SASI, 2025)
Introduction: This article examines the legal challenges in the absence of specific regulations governing group companies (holding) in Indonesia, especially within State-Owned Enterprises (SOEs). The core issue lies in determining the liability of the parent company for losses incurred by its subsidiaries due to unclear corporate accountability structures and control relationships in the SOE holding framework.Purposes of the Research: The purpose of this study is to analyze the legal framework that governs the relationship between a parent company and its subsidiaries in SOE holding structures, with particular attention to the responsibility of corporate organs in addressing subsidiary business risks.Methods of the Research: This study applies normative juridical research using a statutory and case-based approach. The analysis is based on secondary legal materials and is supported by comparative law methods from other jurisdictions to evaluate the application of doctrines such as piercing the corporate veil and business judgment rule.Results of the Research: The findings show that the doctrine of piercing the corporate veil may apply when the parent company’s actions result in harm to subsidiaries. However, corporate organs remain protected under the business judgment rule if acting in good faith. This study contributes by offering a legal framework for parent-subsidiary accountability in SOE holdings and comparing it with international practices.